1979
DOI: 10.1111/j.1365-2125.1979.tb00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesterolone: thrombosis during treatment, and a study of its prothrombotic effects.

Abstract: 1. We describe a patient who developed deep vein thrombosis after commencing treatment with the synthetic androgen, mesterolone (Pro‐ Viron). 2. To investigate the potential thrombogenic action of this drug, a 21 day course of mesterolone (100 mg/day) was given to nine healthy male volunteers. 3. No significant change after treatment occurred in any of the blood tests performed (clotting times, Factor VIII coagulant activity, Factor VIII related antigen, antithrombin III activity, fibrinogen, fibrinogen‐fibrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Several studies have suggested an increase in fibrinolysis with androgen administration (6)(7)(8) and plasma testosterone levels are positively correlated with tPA and negatively correlated with PAI activity in hyperlipidaemic men (22). Others have found no changes in fibrino lysis during 3 weeks of treatment with the synthetic androgen mesterolone (2). The fall in PAI found here may be the mechanism for the increase in fibrinolysis previously reported.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Several studies have suggested an increase in fibrinolysis with androgen administration (6)(7)(8) and plasma testosterone levels are positively correlated with tPA and negatively correlated with PAI activity in hyperlipidaemic men (22). Others have found no changes in fibrino lysis during 3 weeks of treatment with the synthetic androgen mesterolone (2). The fall in PAI found here may be the mechanism for the increase in fibrinolysis previously reported.…”
Section: Discussionsupporting
confidence: 56%
“…investigated as a possible hormonal male contraceptive ( I ) . There is increasing concern that anabolic steroid abuse may eause thrombo embolism, but the evidence so far is largely anecdotal (2)(3)(4). In animal studies, testosterone caused an increase in experimentally-induced thrombosis (5), but synthetic androgens, in particular stanozolol, increase fibrinolysis (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…In adults, associations between anabolic/androgenic steroid abuse and acute arterial or venous thrombosis have been demonstrated 13–17. Underlying mechanisms have been suggested to involve interactions of androgens with platelet aggregation,18 coagulation and fibrinolytic proteins, and the vasculature 19.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of thromboembolism following the abuse of anabolic steroids (Lowe et al, 1979;Ferenchick, 1990;Robinson & Wise, 1993). There are reports of thromboembolism following the abuse of anabolic steroids (Lowe et al, 1979;Ferenchick, 1990;Robinson & Wise, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of T on the haemostatic system is largely unknown. There are reports of thromboembolism following the abuse of anabolic steroids (Lowe et al, 1979;Ferenchick, 1990;Robinson & Wise, 1993). However, an increase in fibrinolysis has been described with stanazolol (Kluft et al, 176 H. M. Buckler et al ᭧ 1998 Blackwell Science Ltd, Clinical Endocrinology, 49, 173-178…”
Section: Discussionmentioning
confidence: 99%